2013
DOI: 10.1016/j.nrl.2012.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Red de cuidadores informales de los pacientes con demencia en la provincia de Alicante, descripción de sus características

Abstract: Women dominate the network of caregivers for dementia patients, whether as principal caregivers, supporting caregivers or formal caregivers (in all cases, they have only limited training in dementia management). Males are largely absent. Better knowledge of the care structure supporting dementia patients may be helpful in the overall management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
2
10
0
8
Order By: Relevance
“…8 Generally, it is the daughters and wives who assume the care 9 and among the main reasons that lead them to take on the family members; this caregiver role is the moral obligation than dignification and personal satisfaction that takes them to take care of a member of their family. 10,11 The average dedication of a caregiver is 10 hours a day and in years, between 7 and 10 years. 12 In general, Alzheimer's patients evolve in three large stages according to Alberca and López 13 : phase I or initial, is an insidious period, difficult to differentiate from a normal aging, in which, the short-term memory loss along with other cognitive abilities deficits, such as: language alteration, execution and spatio-temporal disorientation, are appreciable.…”
Section: Introductionmentioning
confidence: 99%
“…8 Generally, it is the daughters and wives who assume the care 9 and among the main reasons that lead them to take on the family members; this caregiver role is the moral obligation than dignification and personal satisfaction that takes them to take care of a member of their family. 10,11 The average dedication of a caregiver is 10 hours a day and in years, between 7 and 10 years. 12 In general, Alzheimer's patients evolve in three large stages according to Alberca and López 13 : phase I or initial, is an insidious period, difficult to differentiate from a normal aging, in which, the short-term memory loss along with other cognitive abilities deficits, such as: language alteration, execution and spatio-temporal disorientation, are appreciable.…”
Section: Introductionmentioning
confidence: 99%
“…The rate is higher than that found by Toribio-Díaz et al (2013) in a sample of 129 Spanish individuals with moderately advanced Alzheimer's dementia, among whom only 11.6% had hired caregivers. 35 It was observed that 41.8% of the sample presented a CVA episode. A similar rate (46.7%) was found by Arizon et al (2008) in elderly people institutionalized in Israel.…”
Section: Discussionmentioning
confidence: 98%
“…Esta descripción coincide con la realizada en otros estudios11,24 .Actualmente, los cambios sociales afectan al sistema de cuidados informales del paciente dependiente, sobre todo en los roles desempeñados por el sexo femenino (cuidador principal por excelencia), debido a su progresiva incorporación al mercado laboral25 , por lo que pueden ser trascendentales en la atención y en el cuidado futuro de los pacientes dependientes11,26 .Confirmamos,como otros trabajos5,13,15 , que la familia y principalmente la mujer es la responsable de los cuidados de los pacientes con ictus; y que las consecuencias negativas referidas por los cuidadores son los dolores y el cansancio (vitalidad), que podría estar relacionado con la falta de descanso y sueño que referían nuestros cuidadores. Otros estudios 11 sobre cuidadores confirman la presencia de cambios emocionales, ansiedad y trastornos del sueño.En nuestra muestra, entre el 28 y el 58% de los cuidadores presentan un estado de ánimo deprimido; de igual forma que otros estudios 17,27 encuentran que entre un 37-57% de los cuidadores de pacientes con ictus presentan estados psicopatológicos, que estaría en consonancia con nuestro rango.En relación a la sobrecarga, en el estudio de Pinedo 5 sobre cuidadores de pacientes con un ictus obtuvieron una media en la escala de Zarit de 33,62 similar a los nuestros (35,65 puntos), y sensiblemente inferior que el resultado obtenido por Carod et al17 , hecho que podría explicarse por el tiempo que dedican al cuidado de su familiar al día (1 h 30 de media); mientras que en nuestro caso y en Pinedo 5 era muy superior.…”
unclassified